КОЛЛАБОРАТИВНЫЙ ПРОЕКТ КАК ОДИН ИЗ МЕТОДОВ ОБУЧЕНИЯ СТУДЕНТОВ В ПЕДАГОГИЧЕСКИХ ВУЗАХ - Арипова, М.Г. (SCIENCE and SOCIETY, 2020)
The article discusses the method of collaborative design in the class "History of Russian literature" in pedagogical establishments. By the example of a lesson on the topic “Little Tragedies” by A. Pushkin. Creative intent and history of the creation of "Little Tragedies" are presented. Connection with European literature is learnit.